Revision as of 05:57, 16 September 2013 by Mboutin (Talk | contribs)


Practice Problem on Discrete-time Fourier transform computation

Compute the discrete-time Fourier transform of the following signal:

$ x[n]= u[n+2]-u[n-1] $

See these Signal Definitions if you do not know what is the step function "u[n]".

(Write enough intermediate steps to fully justify your answer.)


Share your answers below

You will receive feedback from your instructor and TA directly on this page. Other students are welcome to comment/discuss/point out mistakes/ask questions too!


Answer 1

$ x[n] = u[n+2]-u[n-1] $.

$ X_(\omega) = \sum_{n=-\infty}^{+\infty} x[n] e^{-j\omega n} $

$ = \sum_{n=-2}^{0} x[n] e^{-j\omega n} $

$ = 1+ e^{j\omega} + e^{2j\omega} $

Instructor's comment: Short and sweet. I like that.

Answer 2

Green26 ece438 hmwrk3 rect.png

$ X_{2\pi}(\omega) = \sum_{n=-\infty}^{+\infty} x[n] e^{-j\omega n} $

$ = \sum_{n=-2}^{0} x[n] e^{-j\omega n} $

$ = e^{2j\omega} + e^{j\omega} + 1 $

Instructor's comment: It does help to visualize the signal first.

Answer 3

$ X(\omega) = \sum_{n=-\infty}^{+\infty} (u[n+2] -u[n-1]) e^{-j\omega n} $

$ = \sum_{n=-2}^{+\infty} u[n+2] e^{-j\omega n} - \sum_{n=1}^{+\infty} u[n-1] e^{-j\omega n} $

$ = \sum_{n=-2}^{0} (u[n+2] -u[n-1]) e^{-j\omega n} $

$ = e^{2j\omega} + e^{j\omega} + 1 $

Answer 4

$ x[n] = u[n+2]-u[n-1] $


$ x[n] = ((\delta[-2]) +(\delta[-1]) +(\delta[0])) $ ( Instructor's comment: The right-hand side does not depend on n. Unless your signal is constant, this means you made a mistake.)

so $ X[Z] = e^{2 j \omega} +e^{j \omega} +1 $

Answer 5

$ x[n] = u[n+2] - u[n-1] $

$ X_(\omega) = \sum_{n=-\infty}^{+\infty} x[n] e^{-j\omega n} $

$ X_(\omega) = \sum_{n=-2}^{0} e^{-j\omega n} $

$ X_(\omega) = 1 + e^{j\omega}+ e^{2j\omega} $

Answer 6

from the equation we can get that

$ X(n) = u[n+2] - u[n-1] = \left\{ \begin{array}{l l} 1 & \quad when \quad n = -2,-1,0\\ 0 & \quad \text{else} \end{array} \right. $

Hence, substitute into the DTFT equation,

$ X_(\omega) = \sum_{n = -\infty}^{ \infty} x[n] e^{-j\omega n} $

change the limit to

$ X_(\omega) = \sum_{n = -2}^{ 0} e^{-j\omega n} $

Then, we expand to the normal expression.

$ X_(\omega) = 1 + e^{j \omega} + e^{j 2 \omega} $


Answer 7

$ X(\omega) = \sum_{n=-\infty}^\infty x[n]e^{-j2\omega n} $

$ X(\omega) = e^{-j2\omega n}(\delta (n+2)-\delta (n+1)+\delta (n)) $ (Instructor's comment: The right-hand-side depends on n, but the left-hand-side does not. This means you made a mistake.)

$ X(\omega) = e^{-j2\omega} + e^{-j\omega} + 1 \ $

Answer 8

x[n] = u[n+2]-u[n-1]

$ X(\omega) = \sum_{n=-\infty}^\infty x[n]e^{-j\omega n} $

$ = \sum_{n=-2}^0 x[n]e^{-j\omega n} $

$ = e^{j\omega 2}+e^{j\omega}+1 \ $


Back to ECE438 Fall 2013

Alumni Liaison

Correspondence Chess Grandmaster and Purdue Alumni

Prof. Dan Fleetwood